Isolation and Molecular Identification of Vibrio spp. by Sequencing of 16S rDNA from Seafood, Meat and Meat Products in Libya: A Descriptive Study - S. M. Azwai; E. A. Alfallani; S. K. Abolghait; A. M. Garbaj; H. T. Naas; A. A. Moawad; F. T. Gammoudi; H. M. Rayes; I. Barbieri; I. M. Eldaghayes (Innovations in Microbiology and Biotechnology Vol. 4, 2022)
The main objective of this study was to characterize bacteria isolated from seafood, meat and meat products that may cause foodborne illnesses. We plan to use this data to help create a baseline for future research into foodborne illness in Libya. Several food-borne organisms in the genus Vibrio produce a variety of clinical disorders, including septicemia, cholera, and milder types of gastroenteritis. Vibrio cholerae, Vibrio parahemolyticus, and Vibrio vulnificus are among the Vibrio spp. that are usually related with food-borne transmission. A total of 93 samples (Table 1) of seafood, meat and meat products that includes 21 of shrimps; 5 of clam; 20 of fish; 34 samples of raw meat (10 beef, 9 camel meat, 6 mutton and 9 chickens) and 13 samples of meat products (2 beef sausages, 5 beef burgers, 5 chicken burgers and 1 kebab) were randomly collected from different geographic localities in Libya [Tripoli, Regdalin (120 km west of Tripoli), Janzour (30 km west of Tripoli) and Tobruk (1400 km east of Tripoli)]. Each sample was 250 g in weight. Out of the 93 cultured samples only 48 (51.6%) yielded colonies on Thiosulfate Citrate Bile Salt agar (TCBS) with culture characteristics of Vibrio spp. More than half (n=27) of processed seafood samples (n=46) yielded colonies on TCBS, while only 44.6% of samples of meat and meat products showed colonies on TCBS. Among cultured seafood samples, the highest bacterial count was recorded in clam with a count of 3.8X104 CFU. Chicken burger samples showed the highest bacterial count with 6.5X104 CFU. Molecular analysis of the isolates obtained in this study, showed that 11 samples out of 48 (22.9%) were Vibrio spp. Vibrio parahemolyticus was isolated from camel meat for the first time. Finally, it is empirical to mention that the identity of the retrieved Vibrio parahemolyticus and V. harveyi were presumptively identified using morphological characteristics extracted from morphological cultural characteristics on the selective TCBS agar media.